A study of the perception of the impact of modeling on the development of commitment to action in Decision Conferencing. - Wood, Margaret Ann (Curtin University, 2004)
Managers are increasingly faced with making complex decisions in turbulent organisational environments. This has led to greater information processing demands. Increasingly organisations try to deal with this in such a way that many of these decisions are now made in a group environment. The increase in group decision making has generated a corresponding intensification in the interest in options available to support such decision making. One such approach is a Group Decision Support System (GDSS) referred to as Decision Conferencing. However, Decision Conferencing rests on the unsupported key premise that the computer modeling, which forms an intrinsic part of the process, leads to shared understanding and commitment - the stated goals of the process. The application of Decision Conferencing to important organizational issues continues, yet prior to this study its fundamental premise was both empirically unsupported and potentially under-theorised. This theory-building research demonstrates that the interface between these concepts is more complex than the literature suggests and that the concepts themselves are problematic. Shared understanding is essentially a dependent variable, with factors such as comprehension of the modeling process impacting on the degree to which this is developed. In addition, many aspects of commitment fall outside of the domain of the Decision Conference workshop e.g. the individual’s sense of responsibility and degree of commitment to their profession. The idea of commitment appears to fall more into the arena of managerial responsibility and change management and it is partly how the outcomes are managed after the Decision Conference which will be crucial to their implementation.Within this study it appears that the most a Decision Conference can offer is the ‘buy-in’ or constructive involvement of the individual participant; the assurance of an unassailable case to which all participants have contributed, for the adoption of the outcomes; and the confidence in the outcomes that this brings. All of this suggests that a higher order goal which subsumes these factors should be considered when re-conceptualising the Decision Conferencing experience. It is suggested here that Decision Quality is a more appropriate goal for the Decision Conferencing process. In essence this is an expansion of the existing ‘best bet’ concept already endorsed in the Decision Conferencing literature. The thesis presents a number of conditions for assuring decision quality e.g. a democratic environment for decision making; mutual respect and an encouragement of diversity. It is also argued that it falls to the facilitator to encompass all of these factors. Given the above, it is also suggested that it is appropriate to consider an alternative conceptualization of Decision Conferencing which facilitators of public sector groups might adopt. This revised conceptualization is drawn from complexity theory. Incorporating the findings from this study a more strongly theorised facilitation approach, entitled Quality Facilitation Practice (QFP) has been developed. Taking into account all of the above a revised model for Decision Conferencing in the public sector is presented, incorporating both QFP and the higher order goal of Decision Quality.